2006
DOI: 10.1007/s00296-006-0251-z
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of fibromyalgia, temporomandibular disorder, and masticatory myofascial pain syndromes

Abstract: The purpose of this study was to determine the association of fibromyalgia (FM) with temporomandibular disorder (TMD) and masticatory myofascial pain (MMP). Thirty-one consecutive women diagnosed as having FM according to American College of Rheumatology criteria and 21 consecutive women diagnosed as having TMD were included in this prospective study. All patients were examined by a dentist and a physiatrist to identify the coexistence of FM and TMD. In the FM group, TMD was found in 25 (80%) patients, and onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 3 publications
2
44
0
8
Order By: Relevance
“…On the other hand, other articles also reported that difficult TMD patients report more complaints about generalized body pain 6,8,9,11,13 and that patients with generalized body pain are susceptible to develop facial pain 29 . Although this study has some limitations as the size of the sample and collection of past data, the fact that Group A patients already presented a pain condition prior to the onset of the fibromyalgia could help to understand why they have more severe TMD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other articles also reported that difficult TMD patients report more complaints about generalized body pain 6,8,9,11,13 and that patients with generalized body pain are susceptible to develop facial pain 29 . Although this study has some limitations as the size of the sample and collection of past data, the fact that Group A patients already presented a pain condition prior to the onset of the fibromyalgia could help to understand why they have more severe TMD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of temporal and spatial pain summation also play an important role on central sensitization of these patients 2,3 . The original diagnostic criteria of fibromyalgia does not include the evaluation of the craniofacial area 4,5 , however fibromyalgia patients often present orofacial pain including temporomandibular disorders (TMD) disorders 6,7,8,9 .…”
mentioning
confidence: 99%
“…[14][15][16] Bizim de kliniğimizde daha önce yaptığımız bir çalışmada; 37'si genel vücut ağrısı, diğerleri ise bölgesel ağrı yakın-ması ile polikliniğimize başvuran toplam 124 yaşlı hastanın %37,9'una FMS tanısı konulmuştu. 17 "Santral sensitivite sendromları" adı altında, etiyolojide santral sensitizasyonun rol aldığı ve ortak klinik bulguların gözlendiği bir grup hastalık içinde yer alan FMS'de temel bulgu ağrı olmakla birlikte yorgunluk, uyku bozukluğu, gerilim tipi baş ağrısı, migren, kognitif bozukluk, irritabl barsak sendromu, irritabl mesane sendromu, temporomandibuler disfonksiyon gibi bulgular da gözlen-mektedir. 1,4,7,18 FMS'li hastalarda hâlsizlik ve yorgunluk en sık görülen (%86) semptomlardan olup, irritabl barsak %50'den fazla, baş ağrısı %70, üretral sendrom %12 ve dismenore %43 olarak bildirilmiştir.…”
Section: Discussionunclassified
“…It is a common disorder, found in 1-3% of the general population (5,6), and can manifest as a single disorder (primary fibromyalgia) or associated to other illnesses (concomitant fibromyalgia). In this context, fibromyalgia may be concomitantly present in over 50% of all patients with myofascial pain associated to TPs (7). Some theories have implicated alterations in neurotransmitter regulation, immune function, sleep physiology or hormonal control in the pathogenesis of fibromyalgiaall associated to dysfunction of the limbic system and neuroendocrine axis (5,8,9).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…PHS can be mistakenly diagnosed as a psychological disorder on the basis of the absence of organic alterations capable of accounting for the symptoms (3,10). Joint dysfunction represents one of the musculoskeletal pain syndromes that most often produce muscle pain (3,7). In this case the increase in muscle tension and activity associated to TPs can perpetuate or provoke joint stress, while in some cases joint stress can cause TP activation.…”
Section: Differential Diagnosismentioning
confidence: 99%